Financial Literacy and SME Financial Performance, The Mediating Roles of Marketing Capability and Human Capital - Khairun Amala; Sophia Imari; Wirdah Irawati; Muhammad Basyir; Fakhri Ramadhan (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
This study examines the effect of financial literacy on financial performance and the mediating roles of marketing capability and human capital. A quantitative cross-sectional survey was conducted with 124 respondents, and data were analyzed using PLS-SEM. The results show that financial literacy has a positive total effect on financial performance (? = 0.595). Financial literacy significantly enhances marketing capability (? = 0.446) and human capital (? = 0.396), which in turn positively influence financial performance. Human capital shows the strongest effect (? = 0.544), followed by marketing capability (? = 0.372). Mediation analysis confirms partial mediation, with indirect effects of 0.166 (marketing capability) and 0.215 (human capital). The model explains 63.2% of the variance in financial performance, indicating strong explanatory power. The findings suggest that financial literacy improves financial outcomes both directly and indirectly through capability development. This study contributes by integrating financial literacy theory, resource based view, and human capital theory into a unified mediation framework.